Emplacement Of The Meratus Ultrabasic Massif A Gravity Interpretation - Dr. B Situmorang (Testing Center for Oil and Gas LEMIGAS, 1987)
Based on gravity data, extensive outcrops of igneous ultrahasic rocks at Meranus Range in Southeast Kalimantan have been interpreted as part of oceanic crust emplaced onto the margin of the Sundaland. The Meratus ultrabasic massif appears to be a thin slab with relative thickness of 300 m, thickening to 350 m to the southeast. If terpentinization of ulrabasie rocks is taken into account, the thickness of the allochtonous masses will increase to 780 m. Considering the occurrence of similar rocks in Kukusan Mts, Laut Islard and the South Am of Sulawesi, we suggest that the Metsaas massif forms part of a larger oceanic enustal segment emplaced during the Middle Cretaceous obducrion.